Evaluasi Kinerja Guru dalam Peningkatan Mutu Pendidikan pada Masa Pandemi Covid-19 di SD Negeri 14 Banyuasin II - Irawan, Bambang (Journal of Innovation in Teaching and Instructional Media, 2021)
During the Covid-19 pandemic, this study investigates the performance of teachers at SD Negeri 14 Banyuasin II. This study employed a qualitative method. Interviews, observations, and listings were used to collect data. Teacher performance in preparing lesson plans, teacher performance in implementing learning, teacher performance in assessing learning outcomes, and teacher discipline in learning were summarized as follows. The teacher's performance in learning planning was 92.5 percent, while performance in learning implementation was 70.35 percent, the performance in learning assessment was 91.9 percent, and the work discipline was 79.2 percent, according to the results. Several difficulties can obstruct teacher effectiveness, including the fact that teachers' techniques do not fully complement students' ability to activate their thinking capability and thus participate more actively in learning.